Melville and His Medusae: A Reading of Pierre - Šesnić, Jelena (Array, 2003)
In light of recent gender theories the author argues that Melville, in his only sentimental novel _Pierre_ (1852), uses common gender stereotypes (e. g. woman as temptress) in order to solidify the precarious social status of his young male protagonist. The feminine complex comes to stand misleadingly for the primary source of the young man's failure to assume his expected social position although, in fact, this covers for the more insidious workings of other social hierarchies, not quite represented in Melville's novel.